"K for the way" DJ rhetoric and literacy for twenty-first-century writing studies - Craig, Todd, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
Explores multiliteracies and the ideas of composition, rhetoric, and literacy from the perspective of the hip-hop DJ, conducting a larger qualitative research study that illustrates the DJ as a new media reader, writer, and literary critic.--Provided by publisher.
K for the way: DJ rhetoric and literacy for twenty-first-century writing studies
Foreword / Young Guru -- Planted Seeds Grow Trees: The Impetus for the Urgency of "K for the Way": DJ Rhetoric and Literacy for Twenty-First- Century Writing Studies -- "Itchin' for a Scratch": Pushin' Toward a DJ Rhetoric on the 1s and 2s -- Jackin' for Beats v2.0: The Intertextuality (Re)Mix -- "A Whole Lotta Somethin' from Nufin": Racism, Revision, and Rotating Records: The Hip Hop DJ in Composition Praxis -- "Sista Girl Rock": Women of Color and Hip Hop Deejaying as Raced/Gendered Knowledge and Language -- The Get Down Parts Keeps Gittin' Down: The DJ in the Center of the Comp "Contact Zone" -- "Learn Levels to This Whole Thang . . . Trying to Make a Slow Change": Spinnin' the Words for Comp3.0.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Literacy -- Study and teaching; Hip-hop -- Influence; Music in education; Culturally relevant pedagogy; Disc jockeys